Determinants of Course Grades in Allied Health Sciences Programs. - Chen, Roy K. (Journal of Allied Health)
Past research has shown that there is a pattern of systematic grade inflation in higher education in the U.S. As a result, it is difficult for prospective employers and graduate school admission directors to distinguish bright candidates when recruiting new graduates, The purpose of this study was two-fold: 1) to determine the grading patterns of four academic departments (i.e., rehabilitation services, communication science and disorders, social work, and nursing) in an allied health college at a large public university over time, and 2) to consider which instructor demographic factors and course characteristics might influence the grading patterns. Using an archival data set, the grades for 1,892 course sections over 12 semesters were examined. The results showed that the Department of Social Work had the highest semester GPAs, and that approximately 20% of the variance in course GPAs was due to course characteristics, with instructor characteristics only explaining 3% of the variance. Implications and directions for future research are discussed.